Elucidation of the Nano-Mechanical Property Evolution of 3D-Printed Zirconia - Joshua Z. R. Dantzler; Diana Hazel Leyva; Amanda L. Borgaro; Md Shahjahan Mahmud; Alexis Lopez; Saqlain Zaman; Sabina Arroyo; Yirong Lin; Alba Jazmin Leyva (Micro, 2025)
Understanding the mechanical properties of three-dimensional (3D)-printed ceramics while keeping the parts intact is crucial for advancing their application in high-performance and biocompatible fields, such as biomedical and aerospace engineering. This study uses non-destructive nanoindentation techniques to investigate the mechanical performance of 3D-printed zirconia across pre-conditioned and sintered states. Vat photopolymerization-based additive manufacturing (AM) was employed to fabricate zirconia samples. The structural and mechanical properties of the printed zirconia samples were explored, focusing on hardness and elastic modulus variations influenced by printing orientation and post-processing conditions. Nanoindentation data, analyzed using the Oliver and Pharr method, provided insights into the elastic and plastic responses of the material, showing the highest hardness and elastic modulus in the 0° print orientation. The microstructural analysis, conducted via scanning electron microscopy (SEM), illustrated notable changes in grain size and porosity, emphasizing the influencing of the printing orientation and thermal treatment on material properties. This research uniquely investigates zirconia’s mechanical evolution at the nanoscale across different processing stages—pre-conditioned and sintered—using nanoindentation. Unlike prior studies, which have focused on bulk mechanical properties post-sintering, this work elucidates how nano-mechanical behavior develops throughout additive manufacturing, bridging critical knowledge gaps in material performance optimization.